A Four-Feet Walking-Type Rotary Piezoelectric Actuator with Minute Step Motion - Yingxiang Liu; Yun Wang; Junkao Liu; Dongmei Xu; Kai Li; Xiaobiao Shan; Jie Deng (Sensors, 2018)
A four-feet walking-type rotary piezoelectric actuator with minute step motion was proposed. The proposed actuator used the rectangular motions of four driving feet to push the rotor step-by-step; this operating principle was different with the previous non-resonant actuators using direct-driving, inertial-driving, and inchworm-type mechanisms. The mechanism of the proposed actuator was discussed in detail. Transient analyses were accomplished by ANSYS software to simulate the motion trajectory of the driving foot and to find the response characteristics. A prototype was manufactured to verify the mechanism and to test the mechanical characteristics. A minimum resolution of 0.095 μrad and a maximum torque of 49 N·mm were achieved by the prototype, and the output speed was varied by changing the driving voltage and working frequency. This work provides a new mechanism for the design of a rotary piezoelectric actuator with minute step motion.